Unravelling genetic diversity in pointed gourd (Trichosanthes dioica) genotypes from India’s Eastern plateau and hill region: Insights from morphological and molecular markers - Ankit Kumar Sinha; P. Bhavana; A.K. Singh; J.K. Ranjan; H. Choudhary; G.P. Mishra; K. Thamilarsi; Paresh Chaukhande; Reshma Shinde; Prakash Kumar; Jitendra Rajak; Sajiya Ekbal (Journal of Genetic Engineering and Biotechnology, 2025)
Pointed gourd (Trichosanthes dioica Roxb.), a nutritionally rich, dioecious cucurbit crop native to India, holds immense potential for enhancing food security, yet its genetic diversity remains underexplored, limiting breeding efforts for improved yield and quality. This study addresses this gap by evaluating the genetic diversity of 46 pointed gourd genotypes using morphological traits and ISSR markers. Principal component analysis (PCA) revealed three principal components explaining 72.53% of the total morphological variation, with fruit weight (0.47), pulp weight (0.46), and fruit volume (0.44) as primary contributors to PC1, and total fruit yield (0.53) and number of fruits per plant (0.49) dominating PC2. The PCA biplot identified five distinct genotype groups, highlighting significant diversity. Molecular analysis with sixteen polymorphic ISSR markers generated 96 bands, of which 76 were polymorphic (78.91%), with Polymorphism Information Content (PIC) ranging from 0.35 to 0.47. Cluster analysis grouped genotypes into seven morphological and two primary molecular clusters, the latter further divided into six sub-clusters. Swarna Rekha, Swarna Suruchi, Swarna Alaukik, HAP 24, HAP 78, and HAP 113 were identified as highly diverse. These findings demonstrate that integrating morphological and molecular markers effectively uncovers genetic variability, providing a robust foundation for breeding programs. Future work will focus on leveraging these diverse genotypes for hybridization to develop high-yielding, nutrient-rich cultivars and exploring additional molecular markers to further refine genetic diversity assessments.